Risk Perception in the Construction Industry: Differences Between Italian and Migrant Workers Before and After a Targeted Training Intervention. (May 2021) - Ricci, Federico; Bravo, Giulia; Modenese, Alberto; Pasquale, Fabrizio De; Ferrari, Davide; Gobba, Fabriziomaria
We developed a visual tool to assess risk perception for a sample of male construction workers (forty Italian and twenty-eight immigrant workers), just before and after a sixteen-hour training course. The questionnaire included photographs of real construction sites, and workers were instructed to select pictograms representing the occupational risks present in each photograph. Points were awarded for correctly identifying any risks that were present, and points were deducted for failing to identify risks that were present or identifying risks that were not present. We found: (1) Before the course, risk perception was significantly lower in immigrants compared to Italians ( p  < .001); (2) risk perception improved significantly ( p  < .001) among all workers tested; and (3) after the training, the difference in risk perception between Italians and immigrants was no longer statistically significant ( p  = .1086). Although the sample size was relatively small, the results suggest that the training is effective and may reduce the degree to which cultural and linguistic barriers hinder risk perception. Moreover, the use of images and pictograms instead of words to evaluate risk perception could also be applied to nonconstruction workplaces.